Enhanced Optomotor Efficiency by Expression of the Human Gene Superoxide Dismutase Primarily in Drosophila Motorneurons. (June 2013) - Petrosyan, Agavni; Gonçalves, Oscar F.; Hsieh, I-Hui; Phillips, John P.; Saberi, Kourosh
Abstract Mutation of the human gene superoxide dismutase (hSOD1) triggers the fatal neurodegenerative motorneuron disorder, familial amyotrophic lateral sclerosis (ALS or Lou Gehrig's disease). Broad expression of this gene in Drosophila has no effect on longevity or functional senescence. We show here that restricting expression of human SOD1 primarily to motorneurons of Drosophila has significant effects on optomotor efficiency during in-flight tracking of rapidly moving visual targets. Under high-stress workloads with a recursive visual-motion stimulus cycle, young isogenic controls failed to track rapidly changing visual cues, whereas their same-aged hSOD1-activated progeny maintained coordinated in-flight tracking of the target by phase locking to the dynamic visual movement patterns. Several explanations are considered for the observed effects, including antioxidant intervention in motorneurons, changes in signal transduction pathways that regulate patterns of gene expression in other cell types, and expression of hSOD1 in a small set of neurons in the central brain. That hSOD1 overexpression improves sensorimotor coordination in young organisms may suggest possible therapeutic strategies for early-onset ALS in humans.